Problems and Expectations on International Journal Publication by Faculty Members of the English Department of Islamic Institutes in Indonesia - Paidi Gusmuliana; Safnil Arsyad; Noermanzah Noermanzah; Eka Apriani; Syafryadin Syafryadin (STAI Hubbulwathan Duri, 2022)
Indonesian faculty members in Islamic Institutes in Indonesia are expected to publish their research results in reputable international journals such as those published in English. This study aims to investigate the problems and expectation by faculty members from publishing articles in reputable international journals. A mix-method was adopted in this study questionnaire and depth interviews for gathering primary data. The sample of the study was 100 faculty members at the English Department of Islamic Institutes in Indonesia. The result shows that some problems were faced by the lecturers to publish their articles in reputable international journals: lack of references and difficulties related to academic writing, consuming long time and high costs associated with international publishing, and no reward or for those who can succeed in reputable international journals. However, there are some possible expectations to encourage the lecturers’ international journal publication: frequently attend seminars and workshops on how to write and publish in international journals, practice writing articles collaboratively with the help of a mentor or experienced writer, always revise the article drafts following the suggestion and correction from journal editors or reviewers, and government or institution can support adequate references and costs in the order they fell confident to publish in reputable international journals.